2018
DOI: 10.3390/proteomes6010009
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Profiling of Diabetic Mellitus Patient Urine for Discovery of Biomarkers by Comprehensive MS-Based Proteomics

Abstract: Diabetic mellitus (DM) is a disease that affects glucose homeostasis and causes complications, such as diabetic nephropathy (DN). For early diagnosis of DN, microalbuminuria is currently one of the most frequently used biomarkers. However, more early diagnostic biomarkers are desired in addition to microalbuminuria. In this study, we performed comprehensive proteomics analysis of urine proteomes of diabetic mellitus patients without microalbuminuria and healthy volunteers to compare the protein profiles by mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…The average number of identified proteins in individual urine samples was 613 and 589 in the AD and control groups, respectively. This is comparable to previous reports [13, 33, 34]. Recent studies have found that systemic changes, such as insulin resistance, atherosclerosis, and increased inflammation underlie the development of AD [7, 8, 9].…”
Section: Discussionsupporting
confidence: 90%
“…The average number of identified proteins in individual urine samples was 613 and 589 in the AD and control groups, respectively. This is comparable to previous reports [13, 33, 34]. Recent studies have found that systemic changes, such as insulin resistance, atherosclerosis, and increased inflammation underlie the development of AD [7, 8, 9].…”
Section: Discussionsupporting
confidence: 90%
“…Bjornstad et al., recently reported the relationships between markers of tubular injury and intrarenal hemodynamic function in adults with and without type 1 diabetes ( 44 ). Hirao et al., reported the discovery of a useful biomarker for EDN discovery by proteomics analysis of urine proteomes of DM patients without microalbuminuria and healthy volunteers ( 45 ). Cheung et al.…”
Section: Discussionmentioning
confidence: 99%
“…Improvements to LC-MS instrumentation have led to a series of studies reporting an increasing number of proteins that constitute the healthy human urine proteome, with Zhao et al [176] reporting more than 6000 proteins. This has caught the attention of organizations seeking non-invasive biomarkers, including HUPO which has dedicated the Human Kidney and Urine Proteome Project (HKUPP) specifically to the analysis of urinary biomarkers [177]. The challenges associated with urinary proteomics studies include inter-patient variability since urine protein concentrations depend on kidney filtration and reabsorption performance which greatly fluctuates within a population.…”
Section: Urine-based Proteomicsmentioning
confidence: 99%